2004
DOI: 10.1111/j.1574-6968.2004.tb09554.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation ofElaeagnus-compatibleFrankiafrom soils collected in Tunisia

Abstract: The occurrence and diversity of Frankia nodulating Elaeagnus angustifolia in Tunisia were evaluated in 30 soils from different regions by a Frankia-capturing assay. Despite the absence of actinorhizal plants in 24 of the 30 soils, nodules were captured from all the samples. Eight pure strains were isolated from single colonies grown in agar medium. On the basis of 16S rRNA and GlnII sequences, seven strains were clustered with Frankia, colonizing Elaeagnaceae and Rhamnaceae in two different phylogenetic groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(15 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Frankia cluster 2 dispersal outward from the Coriaria myrtifolia rhizosphere While the presence of Frankia cluster 2 (the host compatible microsymbionts) and cluster 4 (asymbiotic Frankia that are often isolated from Coriaria nodules; Mirza et al, 1992;Gueddou et al, 2017) was expected, the occurrence of cluster 1 and the superabundance of cluster 3 in C. myrtifolia nodule, root, and rhizosphere was surprising. As previously stated, clusters 1 and 3 are known to ubiquitously distributed in soils independent to the presence of compatible host-plants (Paschke and Dawson, 1992;Nalin et al, 1997;Gtari et al, 2004). Cluster 4 is also known to be found free-living in soil (Wolters et al, 1997).…”
Section: Rhizocompartment Microbiomesmentioning
confidence: 75%
See 1 more Smart Citation
“…Frankia cluster 2 dispersal outward from the Coriaria myrtifolia rhizosphere While the presence of Frankia cluster 2 (the host compatible microsymbionts) and cluster 4 (asymbiotic Frankia that are often isolated from Coriaria nodules; Mirza et al, 1992;Gueddou et al, 2017) was expected, the occurrence of cluster 1 and the superabundance of cluster 3 in C. myrtifolia nodule, root, and rhizosphere was surprising. As previously stated, clusters 1 and 3 are known to ubiquitously distributed in soils independent to the presence of compatible host-plants (Paschke and Dawson, 1992;Nalin et al, 1997;Gtari et al, 2004). Cluster 4 is also known to be found free-living in soil (Wolters et al, 1997).…”
Section: Rhizocompartment Microbiomesmentioning
confidence: 75%
“…Isolation of many Frankia strains in pure culture is strong indirect evidence of the ability of strains to thrive asymbiotically in soils. Infective units from clusters 1, 3 and 4 have been shown to be ubiquitously distributed in soils around the world, (Paschke and Dawson, 1992;Nalin et al, 1997;Gtari et al, 2004) even in newly deposited glacial till, volcanic lava deposits, and young sand dunes prior to colonization by host plants (Young et al, 1992). Moreover, Frankia strains from cluster 1 were found to occur abundantly in non-host rhizosphere (Smolander, 1990) and fresh lava deposit with the volcanophile actinorhizal plant species Myrica and Casuarina (Burleigh and Dawson, 1994;Yamanaka and Okabe, 2006;Kurten et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…DNA extraction from root nodules was performed as described by Gtari et al 20 . Individual lobe from the 44 root nodules were surface sterilized as described for microsymbiont isolation protocol, ground in nitrogen liquid and taken up in the extracting buffer (100 mmol l −1 Tris-HCl [pH 8]; 20 mmol l −1 EDTA [pH8.2]; 1.4 M NaCl, and 2% w/v cetyl trimethyl ammonium bromide; CTAB).…”
Section: Methodsmentioning
confidence: 99%
“…35,36 Alongside with the asymbiotic Frankia strains, the protocol used in the present study permitted the isolation of several other actinobacteria which were affiliated to Micrococcus, Micromonospora, Nocardia, Plantactinospora, and Streptomyces genera. Numerous are the studies which reported the isolation of non-Frankia actinobacteria from actinorhizal root nodules 18,20,34,[37][38][39][40][41][42][43][44][45] as it was shown before for legume nodules which contain both rhizobial and non-rhizobial bacteria. 46,47 Three type strains; Micromonospora coriariae 42 ; Nocardia casuarinae 44 and Nocardia alni 48 have been isolated respectively from Coriaria; Casuarina and Alnus root nodules.…”
mentioning
confidence: 99%
“…Furthermore, another study revealed that the alliance of arbuscular mycorrhizal (Glomus mosseae) and rhizobial (R. leguminosarum) symbioses alleviated damage to clover (Trifolium repens) by root hemiparasitic Pedicularis species [42]. The N2-fixing Frankia, one genus belonging to the actinobacteria group, form the actinorhizal nodules with actinorhizal plants, and promote the growth and abiotic resistance for several woody plants, such as Alnus rubra, Hippophae tibetana, Elaeagnus angustifolia, and Casuarina glauca [30,[43][44][45][46]. Root nodule formation in plants by Frankia spp.…”
Section: Plant Growth-promoting Bacteriamentioning
confidence: 99%